Effects of early diagnosis of the wrist over-use syndrome on the treatment - Adnana Talić Tanović; Edina Tanović; Mevludin Mekić; Ivanka Mađar Šimić; Adnan Papović; Hadžan Konjo (Medicinski glasnik, 2018)
Aim: To demonstrate the effects of early diagnosis of overuse syndrome in the wrist on healing, pain intensity and quick recovery to daily work and sport activities. Methods: This clinical retrospective study included 60 patients of both sexes aged from 22 to 44 years, with pain in the wrist and clinical signs of creeping tenosynovitis. Patients were divided into two groups: the first group-persons doing sports activity, and the second group-patients who did not deal with sports activities. Results: Females in 31 (51.7%) cases compared to males with 29 (48.3%) were slightly more represented in the total sample. Patients with injuries due to sports activities had previously reported to the physician and the diagnosis was set at an average of 3.1±0.9 days after the first symptoms (the range of 2-5 days), compared to the patients of the second group whose diagnosis was set at an average of 4.7±1.1 days after the first symptoms (p <0.05). Conclusion: Patients involved in sports activities were more motivated for faster recovery, they had earlier doctor's examination with rapid reduction of subjective symptoms during intensive physical therapy.
Keywords: forearm tendinitis; overstretch; inflammation; conservative therapy over-use syndrome; early diagnosis; pain; wrist joint